Pendampingan dan Pemulihan Trauma Pasca Erupsi Gunung Semeru Pada Masyarakat Desa Curah Kobokan dan Supit Urang Kabupaten Lumajang - Yayuk Sulistiyowati; Sri Indah; Luh Dina Ekasari; Ahmad Mukoffi; Rizki Aprilia Dwi Susanti; Sukarno Himawan Wibisono (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service was carried out to alleviate trauma and to maintain health protocols for the community in the refugee camps. In the camps, the communities see changes in their health and economic conditions. The program involved problem solvings through mentoring and trauma recovery assistance for mothers, fathers, children, and the elderly from Curah Kobokan Village and Supiturang Villang, Lumajang Regency. The aims of this service are to increase the frequency of psychological support provided to victims of the Mount Semeru eruption and to accelerate the community’s mental and economic rehabilitation. This assistance is critical because the community has gained some positive impacts such as feeling less burdened and their mental health is improving as a result of past mentoring and assistance activities.